Pemanenan Air Hujan Ex-Situ oleh Masyarakat Petani untuk Efektivitas Air Irigasi di Pertanian Lahan Kering, Kabupaten Gunungkidul, Yogyakarta: Ex-Situ Rainwater Harvesting by Community Farmers for Irrigation Water Effectiveness in Dryland Agriculture, Gunungkidul District, Yogyakarta - Bimantio, Mohammad Prasanto; Noviyanto, Amir; Jaya, Galang Indra; Raharjo, Dedy Tri; Keviana, Agesty; Suparyanto, Teddy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The karst landscape in Gunungkidul Regency faces major challenges in the agricultural sector, mainly due to limited water availability and dependence on rainfed farming systems. To overcome these challenges, a community service program was implemented by introducing rainwater harvesting and drip irrigation technology to the Giri Muda Farmer Group. This activity aims to increase water availability and water use efficiency in drylands through the application of environmentally friendly technology. The community service method includes an initial survey, system design planning, installation of rainwater harvesting and drip irrigation installations, and technical training for farmers on system operation and maintenance. The evaluation of the activities showed a significant increase in understanding and skills, which had a positive impact on horticultural agricultural productivity. The technology was well received by farmers and has great potential to be developed in the Gunungkidul region and other similar areas. This service program not only succeeded in increasing agricultural productivity in drylands but also contributed to mitigating the impacts of climate change.